Combining Ability Analysis for Yield and Yield Components in Some Important Upland Rice Germplasms of Nagaland - KOLOM, R.; CHANGKIJA, S.; SHARMA, M.B. (Indian Journal of Hill Farming, 2015)
Combining ability analysis for yield and yield components in some important upland rice germplasms of Nagaland was carried out in rice through line x tester analysis of 45 intervarietal crosses developed by crossing 3 testers with 15 lines along with parents and checks. The 45 crosses along with 18 parents and three standard checks were grown in a randomized block design with three replications and were evaluated for early flowering and maturity along with grain yield per plant and other yield components. The experiments were conducted at the Main Scheme Farm, ICAR Research Complex for NEH Region, NagalandCentre, Jharnapani, Medziphema, Nagaland in kharif 2009 and 2010. Analysis of variance for line x tester revealed highly significant differences between the lines x tester for the characters studied except for effective tillers per hill, filled grains per panicle and unfilled grains per panicle with sca variance (Ïƒ2s) and non- additive (Ïƒ2D) variance components higher than genetic variance (Ïƒ2g) and additive (Ïƒ2A) variance for almost all the characters under study. The estimates of gca effects indicated that, Koyapvu Tsok, Manchio TsÃ¼k among lines and RCM-5 and Teke among testers are good general combiners for grain yield per plant. Out of the 45 crosses, 21 crosses exhibited positive sca effects for grain yield per plant. The best sca effects were observed in the cross, Leikhumo (T) x Teke for plant height, which also showed best sca effects for filled grains per panicle.